Answer:
(2,-4)
Step-by-step explanation:
when reflecting across the Y-axis from quadrant 3 to quadrant 4, a sign change from (-,-) to (+,-) would occur.
f<span>(x)</span>=<span>x^2</span>−<span>6
</span>Replace <span>f<span>(x)</span></span> with <span>yy</span>.
<span>y=<span>x^2</span>−<span>6
</span></span>Interchange the variables.
<span>x=<span>y2</span>−6
</span>Solve for <span>yy</span><span>.
</span>
Move <span><span>−6</span><span>-6</span></span> to the right side of the equation by subtracting <span><span>−6</span><span>-6</span></span> from both sides of the equation.<span><span><span>y2</span>=6+x</span><span><span>y2</span>=6+x</span></span>Take the <span><span>square</span><span>square</span></span> root of both sides of the <span><span>equation</span><span>equation</span></span> to eliminate the exponent on the left side.<span><span>y=±<span>√<span>6+x</span></span></span><span>y=±<span>6+x
</span></span></span>The complete solution is the result of both the positive and negative portions of the solution.
Tap for more steps...
<span>y=<span>√<span>6+x</span></span>,−<span>√<span>6+x</span></span></span>
Solve for y<span> and replace with </span><span><span>f^<span>−1</span></span><span>(x).
</span></span>
<span>Answer is f<span>−1</span></span><span>(x)</span>=<span>√<span>6+x</span></span>,−<span>√<span>6+<span>x</span></span></span>
Answer:for ax^2+bx+c=0 the discriminant is b^2-4ac
there are 3 basic cases of what happens for different discriminants
1. if the discriminant is less than 0, then there are no real zeroes
2. if the discriminant is 0, then it has 1 zero
3. if the discriminant is greater than 0, it has 2 zeroes
so given
0=3x^2-7x+4
a=3,b=-7,c=4
thus the discriminant is (-7)^2-4(3)(4)=49-48=1
the discriminant is 1. 1 is positive, thus the equation has 2 zeroes because the discriminant is greater than 0
the answer is the equation has two zeroes because the discriminant is greater than 0
Step-by-step explanation:
Answer:
C
Step-by-step explanation:
400-160=240
240/4=60